Schaeffer's Solfège, Percussion, Audio Descriptors: Towards an Interactive Musical System - Freire, Sérgio; Padovani, José Henrique; Campos, Caio Costa (Vortex Music Journal, 2022)
Pierre Schaeffer's typomorphology (1966) proposes seven criteria of musical perception for the identification and qualification of sound objects, which form the basis of his musical theory. This Solfège fits well into contexts where pitch is not the dominant dimension. Relying on similarities between the practice of reduced listening and the utilization of low-level audio descriptors, we present the first version of a real-time setup in which these descriptors are applied to qualify percussive sounds. The paper describes the tools and strategies used for addressing different criteria: envelope followers with different window sizes and filtering; detection of transients and amplitude modulations; extraction and counting of spectral components; estimation of intrinsic dissonance and spectral distribution; among others. The extracted data is subjected to simple statistical analysis, producing scalar values associated with each segmented object. Finally, we present a variety of examples.